Aquatic Insects of New York Salt Marsh Associated with Mosquito Larval Habitat and their Potential Utility as Bioindicators - Rochlin, I.; Dempsey, M. E.; Iwanejko, T.; Ninivaggi, D. V. (Journal of Insect Science, 2011)
The aquatic insect fauna of salt marshes is poorly characterized, with the possible exception of biting Diptera. Aquatic insects play a vital role in salt marsh ecology, and have great potential importance as biological indicators for assessing marsh health. In addition, they may be impacted by measures to control mosquitoes such as changes to the marsh habitat, altered hydrology, or the application of pesticides. Given these concerns, the goals of this study were to conduct the first taxonomic survey of salt marsh aquatic insects on Long Island, New York, USA and to evaluate their utility for non-target pesticide impacts and environmental biomonitoring. A total of 18 species from 11 families and five orders were collected repeatedly during the five month study period. Diptera was the most diverse order with nine species from four families, followed by Coleoptera with four species from two families, Heteroptera with three species from three families, then Odonata and the hexapod Collembola with one species each. Water boatmen, Trichocorixa verticalis Fieber (Heteroptera: Corixidae) and a shore fly, Ephydra subopaca Loew (Diptera: Ephydridae), were the two most commonly encountered species. An additional six species; Anurida maritima Guérin-Méneville (Collembola: Neanuridae), Mesovelia mulsanti White (Heteroptera: Mesovelidae), Enochrus hamiltoni Horn (Coleoptera: Hydrophilidae), Tropisternus quadristriatus Horn (Coleoptera: Hydrophilidae), Dasyhelea pseudocincta Waugh and Wirth (Diptera: Ceratopogonidae), and Brachydeutera argentata Walker (Diptera: Ephydridae), were found regularly. Together with the less common Erythrodiplax berenice Drury (Odonata: Libellulidae), these nine species were identified as the most suitable candidates for pesticide and environmental impact monitoring due to abundance, position in the food chain, and extended seasonal occurrence. This study represents a first step towards developing an insectbased index of biological integrity for salt marsh health assessment.